An introduction to professional and executive coaching - Boysen-Rotelli, Sheila (Contemporary trends in organization development and change., 2020)
"The coaching profession is growing and innovating. According to the International Coaching Federation (ICF), coaching earns over $2 Billion per year with over 100,000 practitioners of coaching. This book is both practitioners and scholars of executive coaching. Coaching is an exciting and powerful skillset that allows individuals to empower others and helps individuals to generate awareness that opens the door for great levels of success. The approach of this book is to look at the theoretical framework of coaching as it applies to the actual practice of coaching others and groups. It is important to ground practice in theory and research to bring together the researched framework to help to inform the approach. There is an old proverb that states: "Theory is when you know everything but nothing works. Practice is when everything works but no one knows why." The approach of this book will enable the student with the theory, the processes and the skills to coach in a way that works and to be able to understand the why behind the success as well as make it replicable"--